2014
DOI: 10.1111/jvs.12180
|View full text |Cite
|
Sign up to set email alerts
|

Niche breadth of oligarchic species in Amazonian and Andean rain forests

Abstract: Aim To test the niche breadth hypothesis (NBH), which states that dominant species have broader environmental tolerances than rare species, focusing on oligarchic species distributions (1) along the gradients of edaphic and climatic individual variables, and (2) within the n‐dimensional environmental frame defined by all edaphic and climatic variability. Location Amazonian and Andean tropical rain forests along a ca. 3000 m elevation gradient, covering an area of 200 × 200 km in northwestern Bolivia. Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
1
20
0
Order By: Relevance
“…Landscape-scale variation in functional community composition results from local-scale specialization of a given species in response to its climate envelope and the filtering of the locally available species pool by physical and chemical soil properties 39 . We here found differences in plant functional community composition across topoedaphic gradients and more generally that sites with lower resource availability contained less diverse plant www.nature.com/scientificreports www.nature.com/scientificreports/ communities than those with ample soil water and nutrient supply ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Landscape-scale variation in functional community composition results from local-scale specialization of a given species in response to its climate envelope and the filtering of the locally available species pool by physical and chemical soil properties 39 . We here found differences in plant functional community composition across topoedaphic gradients and more generally that sites with lower resource availability contained less diverse plant www.nature.com/scientificreports www.nature.com/scientificreports/ communities than those with ample soil water and nutrient supply ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since this hypothesis was proposed by Stevens (1989), it has been confirmed by a number of studies. More recent studies have used the term 'climatic niche breadth' rather than 'climatic variability' to illustrate the ability (range) that can be tolerated by one species (Fisher-Reid et al 2012, Köster et al 2013, Arellano et al 2014. showed that climatic niche breadth, which is the range of climatic condition a species occurs in, explained more variation than the niche position, which is a species' niche relative to the central tendency of climatic conditions in a study region for the geographical range size of monkeyflower species (genus Mimulus).…”
Section: Climatic Niche Breadth Determines Variation In Geographical mentioning
confidence: 99%
“…(), which reported a consistent pattern of dominance by a relatively small but abundant set of tree and palm species, called “oligarchs”, in the upland tropical forests of eastern Ecuador and southern Peru. Since then, evidence has accumulated reinforcing the existence of a general pattern of oligarchic dominance in tropical forest, especially in the neotropics (Svenning, Kinner, Stallard, Engelbrecht & Wright, ; Vormisto, Svenning, Hall & Balslev, ; Macía & Svenning, ; Williams, Viers & Schwart, ; Williams, Trejo & Schwart, ; Macía, ; Arellano, Cala & Macía, ; Arellano et al., ; see Pitman, Silman & Terborgh, ; for a detailed review), whereas “oligarch” refers to abundant and frequent species at regional‐landscape level, “hyperdominant” defines species very abundant and frequent at large geographical scales (e.g., the Amazon basin). Practical implications of the so‐called oligarchic dominance would drastically simplify model parameterization of trophic interactions and critical ecosystem services, such as water, carbon, and nutrient cycling (ter Steege et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, (3) oligarchies are mainly structured by the same niche mechanisms that generate spatial heterogeneity in tree species composition and abundance (Pitman et al., ). Oligarch species usually show broader environmental tolerances than less common ones (Arellano et al., ; Brown, ; Phillips et al., ; Slatyer, Hirst & Sexton, ), but they are not necessarily indifferent to environmental heterogeneity, showing higher abundances in the most favorable habitats (ter Steege et al., ). As a result, beta diversity will increase with environmental heterogeneity, but this increase is mainly driven by differences in oligarchic abundance and not by turnover in species identity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation